Implementasi Model Pembelajaran Cooperative Script untuk Meningkatkan Hasil Belajar dan Kemampuan Kolaborasi Siswa dalam Mata Pelajaran Akidah Akhlak pada Siswa Kelas VII di MTs Negeri 1 Wonosobo - Ardiansyah, Diky; Firdaus; Nasokah (Literasi: Jurnal Pendidikan Guru Indonesia, 2024)
This research role aims to 1) Know the improvement of student learning outcomes after using the Cooperative Script learning model on Aqidah Akhlak subjects; 2) Know the differences in learning outcome of students using the cooperative script learning model using conventional learning; 3) Know the enhancement of student collaborative skills on Aqidah Akhlak subject; 4) Know the difference in collaborative abilities of students who use the Cooperate Script Learning model using traditional learning. This research uses quantitative research design with experimental research methods. The research subjects consisted of seventy-six people who were divided into experimental classes and control classes of students of grade VII at MTs Negeri 1 Wonosobo. Before learning, both classes are given pre-testing. Students in the experimental class are given scripted material using the Cooperative Script learning model while the control class uses the conventional model. Experimental and control classes receive the final test as a posttest. The results are also analysed, analyzed, and disseminated using test-t and gain tests to determine differences in improved learning outcomes. The results of the study showed that there was an improvement in the learning outcome of Akidah Akhlak subjects using the Cooperative Script learning model. This was demonstrated by using the gain test in the experimental class, obtained a result of 0.574. There was a difference between the Aqidah Akhkak learning outcomes using the cooperative script learning model and the conventional model. This was demonstrated by using a t test with t counting > t of the two tables at a significance position of 1% that is obtained 4.66 > 2.644. While collaborative abilities showed that there was an improvement shown by using the gain test in the experimental class, obtaining a result of 0.466. There was a difference in collaborative ability using the Cooperative Script learning model with the conventional model. This is demonstrated by using the gain t test count > t table that is 4.80 > 2.644 and has a higher average than the control class, that is 14.45 > 9.61.